Enhancing the Energy Storage Properties and Breakdown Strength of Lead-Free Bismuth-Sodium Titanate-Based Ceramics Through NaNbO3 Doping - Jingxia Gao; Haizhou Guo; Hongxia Li; Hui Li; Liqin Yue; Rui Wang; Jiangyan Si; Qiaoqiao Zhao; Yangyang Zhang (Crystals)
Dielectric capacitors with a high density of recoverable energy storage are extremely desirable for a variety of uses. However, these capacitors often exhibit lower breakdown strengths and energy efficiency compared to other materials, which poses significant challenges for their practical use. We report on a novel antiferroelectric ceramic system in the present study, (1 − x){0.97[0.985(0.93Bi0.5Na0.5TiO3–0.07BaTiO3)–0.015Er)]–0.03AlN}–xNaNbO3 (x = 0, 10 wt%, 20 wt%, 30 wt%, and 40 wt%), synthesized via a conventional solid-state reaction approach. Here, (Bi0.5Na0.5TiO3–BaTiO3) is denoted as BNT–BT. We observed that varying the NaNbO3 (NN) content gradually refined the grain size of the ceramics, narrowed their hysteresis loops, and transformed their phase structure from antiferroelectric to relaxor ferroelectric. These changes enhanced breakdown strength (Eb), thus increasing the performance of energy storage. Specifically, the recoverable energy density (Wrec) and energy storage efficiency (η), respectively, reached 0.67–1.06 J/cm3 and 44–88% at electric fields of 110–155 kV/cm, with the highest performance observed at 30 wt% NN doping. Additionally, over a broad range of temperature and frequency, the 70 wt% {0.97[0.985(BNT–BT)–0.015Er]–0.03AlN}–30 wt% NN ceramic demonstrated exceptional stability in energy storage. These results demonstrate the significant potential of lead-free(1 − x)({0.97[0.985(BNT–BT)–0.015Er]–0.03AlN}–xNN ceramics for the applications of high-performance energy storage.